Split-award auctions and supply disruptions - Nicolas Fugger; Ulrich Laitenberger (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
Problem Definition: We consider a buyer that needs to source a fixed quantity. She faces several potential suppliers that might fail to deliver. The buyer conducts a procurement auction to determine contract suppliers and can choose between single-sourcing and multi-sourcing. If contract suppliers fail to deliver, the buyer tries to source from non-contract suppliers but has little bargaining power due to time pressure. Academic/Practical Relevance: The mitigation of supply risks plays an important role in procurement practice but attracted little attention in the academic analysis of procurement auctions. Academic research on multi-sourcing procurement auction typically analyzes these auctions as stand-alone events. In contrast, we investigate the influence of the auction design on the post-auction market structure and identify an effect favoring multi-sourcing. The insights provide procurement managers guidance for their sourcing decisions. Methodology: We apply game-theoretical methods to analyze a stylized model in which a cost-minimizing buyer needs to source from profit-maximizing suppliers who might fail to deliver. The buyer conducts a procurement auction to determine contract suppliers and can choose between single-sourcing and multi-sourcing. If contract suppliers fail to deliver, the buyer tries to source from a non-contract supplier. We assume that in this situation, the non-contract supplier has almost all the bargaining power. Results: First, we show that in such a setting multi-sourcing does not only reduce the supply risk but might also yield lower prices than single-sourcing. The sourcing decision affects the post-auction market structure such that being a non-contract supplier becomes less attractive in case of multi-sourcing. Second, if suppliers are heterogeneous regarding their disruption probabilities, less reliable suppliers will bid more aggressively than their more reliable competitors causing an adverse selection problem. Furthermore, we show that attracting an additional supplier can be risky as it can increase the auction price and the buyer's total expenses. Managerial Implications: Our analysis reveals a pro-competitive effect of multi-sourcing. This effect is especially important if the buyer's value for the item is substantially larger than suppliers' production costs and for intermediate disruption probabilities.
Keywords: D44; D47; H57; 330; Adverse selection; auctions; multi-sourcing; supply disruptions; procurement